The pecularities of communicability and adaptability of malaysian and caribbean students - H Thomas; I S Yashchuk (Peoples' Friendship University of Russia (RUDN University), 2010)
This article analyses the diversity of indicators of adaptability and communicability among Caribbean and Malaysian students. It also explores the level of representation of indicators of adaptability and communicability of Caribbean and Malaysian students.